Penerapan Metode Kumon Untuk Meningkatkan Hasil Belajar dalam Pembelajaran Tematik Terpadu Siswa Kelas V MIS Juhari Ilmi - Marziah Marziah; Regina Frederika Sipayung (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2024)
The research was motivated by the low learning outcomes of students seen from the results of the Midterm Examination I of class V MIS Juhari Ilmi, it is known that the percentage of completeness of knowledge scores is still low, this can be seen from the subjects of Indonesian Language 45%, Civics 30%, and Social Studies 60% with the completeness set by the teacher which is 77. So it can be seen that there are still many students who have not met the completeness. The purpose of this study was to describe the improvement of learning outcomes using the Kumon method in class V MIS Juhari Ilmi. This research is a classroom action research with qualitative and quantitative approaches. The research was conducted in two cycles and the results showed an increase in the lesson plan of cycle I with an average of 81.5% good achievement, cycle II 94% very good achievement. Then, the implementation on the educator aspect of cycle I with an average of 83.5% good achievement, cycle II 92% very good achievement, while the implementation on the student aspect of cycle I with an average of 80% good achievement, cycle II 92% very good achievement. Furthermore, the assessment of students in improving learning outcomes in cycle I obtained an average of 76.76 and cycle II an average of 85.9. So it is concluded that using this model can improve student learning outcomes.